Paradigma sonaravnosti je pot do trajnostnih gozdov - Cimperšek, Mitja (Gozdarski vestnik, 2011)
European forestry found the way out of the increasing and frequent stress based disturbances of the forests in the natural or close-to-nature forests. The article deals with theoretical bases of the close-to-nature forestry, its historical development, the decisive role of the forestry phytocoenology in determining of hemeroby, and the most important measures for sustainable forest management.
Keywords: gozdovi; gospodarjenje z gozdovi; gozdno gospodarstvo; sonaravnost; trajnost